Inovações incrementais na prestação de serviços contábeis - Machado, Rosaly (2007)
This work aimed to establish improvement propose in accountancy services with quality dimension, through the use of incremental innovations from businessmen experiences, named by accountant users, and the relationship of these men as accountancy workers. The search is presented in qualitative, quantitative, exploratory and evaluating. The used methodology had as the starting spot the theory content support. Next phase was collecting the information and for this purpose, a questionnaire was used as a tool. In each question there was a suggestion of improvement. A report with explanations about questions that could be considered more difficult was attached to the questionnaire. These questions were handed in to 50 businessmen who use accountancy services in Ponta Grossa. The questions were distributed to accountancy, revenue, and working and workers right area. As the questionnaires were collected, it was noticed that 27 people totally corresponded to the requests of the research, 13 people partially corresponded, and 10 people didn’t show any interest in the subject. Further more the work was focused on semi structured interview. In the methodological sequel, interviews were made with 10 business men, with the aim of going deeper on the information about the quality of these services. To reinforce the results, the services which review themselves not being very satisfactory, had emphasis to the appreciation of these two businessmen, who answered promptly about them. So from the ten dimension of quality used to evaluate the accountant services, the need of knowledge in this area offering strategies in the distribution of the services was predominant. Immediately the cost. The results of me research reviewed that the quality is inherent to the performance of services, not only to the cost. The trust appears as an essential attribute that must always be considered in all levels in accountant services the trust appears as an essential attribute that must always be considered in all levels in accountant services. In this context, these dimensions didn’t d show a satisfactory result, considered by the users in these following services: A) Management of continuous learning, using the experience of business men, putting together with the performance of their activities, B) The values charged for the accountant services, and other expenses with material, C) The execution of the services, pay roll and salaries, as well as the guides for taxes collecting and other related taxes. So, this research shows that the accountant services need to improve. The suggestions for incremental innovations which claimed to be more important by people who answered the questions were: 1) Promoting meetings to develop ideas and experience exchanging with businessmen and accountants. 2) Improving the knowledge by interacting with other areas. 3) Remaining aware of up dating and also all the law changing in the accountancy area. 4) Being always willing to answer the clients promptly in their needs, helping them in any difficulty they may find in their business. 5) Trying to eliminate mistakes from the payroll, finding other ways to collect data in order to accomplish this task. 6) Keep the accountancy launches always at disposal to avoid any delay when handing in accountancy reports. 7) Presenting reports in an explanatory way, showing relevant information that can help people to make decisions. 8) Searching for different ways and strategies to soften the expenses always supported by the law. 9) Making a balance between the cost and the quality of accountancy services. For the reasons presented in this summarize, the objective of the research became real, presenting improvements in accountant services, referred through incremental innovations.